Morphological and molecular characterization of Trichodorus nanjingensis populations occurring in Zhejiang and Beijing, China - LI Xu-qing; LIN Xiao-jia; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版, 2012)
Stubby root nematodes (Trichodorus spp.) are a group of ectoparasitic nematodes that not only affect root growth but also lead to root stagnation of an extensive range of crops by their feeding on plant root cells, and the importance is that some of which are virus vectors and can transmit viruses to many economically important crops such as flowers, vegetables, crops, fruit trees, etc. Until now, more than 50 species have been described in this genus all over the world, by using traditional diagnosis of nematode species based on examination of morphology and morphometrics, which need special taxonomists, is time-consuming and laborious. Recent years, comparative analysis of rDNA genes and their associated spacer regions is becoming a popular tool for species and subspecies identification and construction of phylogenetic trees of many nematode groups, including stubby root nematodes.Among 1 546 soil samples collected from 13 provinces of China, including Beijing, Shandong, Shanxi, Henan, Jiangsu, Anhui, Hunan, Chongqing, Zhejiang, Fujian, Yunnan, Hainan, and Guangdong, 23 populations of Trichodorus nanjingensis were identified from the rhizosphere of Chinese mulberry, ornamental flowers in Zhejiang Province, and orchards in Beijing, by systematical study based on the morphological and rDNA characters.The results showed that the detection rate of T. nanjingensis populations from Beijing accounted for 39.1% of the total samples collected in Beijing, which indicated T. nanjingensis as the dominant nematode species in perennial plants of Beijing. Through the morphological and morphometrical comparisons, slight variation between intra-species was revealed by the populations of T. nanjingensis from Beijing and Zhejiang Province, but two males of population 129 isolated from Prunus blireana and one male of population 088 isolated from Cotoneaster multiflorus from Beijing had one cervical papillae instead of two. The sequence similarity of 18S rDNA between T. nanjingensis populations from Beijing and Zhejiang Province and those submitted in GenBank (AJ439579 and AJ439580) ranged in 99.2% -100.0%. The sequence alignments of ITS1, ITS2 region of rDNA and D2D3 region of 28S RNA gene revealed the consistency between these populations. These results indicate that rDNA sequences can provide useful information for identifying T. nanjingensis from the others.